2011
DOI: 10.1007/s10194-011-0329-1
|View full text |Cite
|
Sign up to set email alerts
|

Headache and migraine during pregnancy and puerperium: the MIGRA-study

Abstract: There is little prospectively gathered data on the course of headaches during pregnancy and postpartum, and the influence of breastfeeding is unclear. This is a large, prospective study, which invited all pregnant women in the catchment area during a defined period. All participants (n = 2,126) filled in questionnaires concerning headache. Among these, a total of 208 women with migraine according to the International Headache Society criteria also filled in detailed headache diaries during pregnancy and the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
2
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 27 publications
(66 reference statements)
1
71
2
11
Order By: Relevance
“…An interesting finding in this study was that the prevalence of migraine attacks without aura was high in the study subjects and did not subside during pregnancy. A recent study reported that women having migraine without aura are more likely to recover than women having migraine with aura (18), but this trend was not observed in our study. It is easy to understand that physical and social problems arising during pregnancy can play a role in the course of migraine during pregnancy.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…An interesting finding in this study was that the prevalence of migraine attacks without aura was high in the study subjects and did not subside during pregnancy. A recent study reported that women having migraine without aura are more likely to recover than women having migraine with aura (18), but this trend was not observed in our study. It is easy to understand that physical and social problems arising during pregnancy can play a role in the course of migraine during pregnancy.…”
Section: Discussioncontrasting
confidence: 56%
“…Most epidemiological studies demonstrated that pregnant women who experience headaches before pregnancy report to have a 55 -90% improvement in the severity of the attack after they become pregnant (15)(16)(17). A large-scale MIGRA study also revealed a significant decrease in the frequency of migraine during pregnancy (18). This could be attributed to stable levels of estrogen and progesterone, along with an increase in beta-endorphin.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Migraine with aura seems to be less affected by pregnancy and menstruation. 94 Despite data supporting estrogen decline as a potential cause of menstrual migraine, the role of estrogen replacement therapy is not clear. The majority of women will have a reduction in menstrual migraine with estrogen therapy; however, in a minority of women estrogen therapy may be associated with increasing frequency of acute migraine attacks, more chronic migraine, and higher risk of stroke.…”
Section: Gender Differences In Treatmentmentioning
confidence: 99%
“…Lactation generally leads to an improvement in the clinical course of migraines during the postpartum period (7). However, few reports have so far focused on migraines during the postpartum period (10), and…”
Section: Introductionmentioning
confidence: 99%